Performance Analysis of Time-Triggered Ether-Networks Using Off-the-Shelf-Components - Florian Bartols and Till Steinbach and Franz Korf and Thomas C. Schmidt (IEEE, 2011)
The performance analysis and validation of distributed real-time systems poses significant challenges due to high accuracy requirements at the measurement tools. A fully synchronized time-scale at ultrafine granularity is not easy to generate. Even though there are several analyzer tools for standard switched Ethernet, these tools cannot be applied in time-triggered networks, since they do not meet the requirements of synchronized packet generation. This paper introduces a low cost and lightweight approach to measure end-to-end latency of time-triggered Ethernet traffic with off-the-shelf components. By using standard computer hardware and a real-time Linux Kernel, it is shown that measurement can be achieved in a resolution of microseconds. Furthermore, a validation with an Ethernet performance analyzer and a mathematical framework is presented to check the given results.